HUBUNGAN PENGETAHUAN DAN SIKAP PERAWAT DENGAN PENANGANAN PASIEN CEDERA KEPALA RINGAN YANG DIRAWAT DI RUANG IGD - -, Fourline (Universitas Audi Indonesia, 2022)
Head injuries occur at 750,000 year and are the leading cause of death in adulthood.Important component in nursing care head injuries is nurse competence which is influencedby knowledge and attitude factors. Providing appropriate nursing care can preventcomplications in head injury patients Purpose: of this study is to determine the Relationshipof Knowledge and Attitude of Nurses with Treatment of Mild Head Injury Patients whoTreate in IGD Ward RSUD Dr. M. Yunus Bengkulu. Methods:This study used descrptivecorrelational approach with cross sectional design. Population in this study were all nurses inIGD Ward RSUD Dr. M. Yunus Bengkulu with the amount of 30 people. Sampling techniquein this study used total sampling. Collecting data in this study used primary data withspreaded questionnaire and and observation directly to the nurses in IGD Ward RSUD Dr. M.Yunus Bengkulu. Data analysis used Chi-Square. Result: of this study showed: (1) from 30sample in IGD Ward RSUD Dr. M. Yunus Bengkulu there were 5 people (16,7%) did notappropriate procedure and 25 people (83,3%) with appropriate procedure; (2) from 30 samplethere were 1 people (3,3%) with lack of knowledge, 10 people (83,3%) with moderateknowledge, and 19 people (63,3%) with good knowledge; (3) from 30 sample there were 6people (20,0%) with negative attitude and 24 people (80.0%) with positive attitude; (4) thereis significant relationship between Knowledge with Treatment of mild head injury patients;(5) there is significant relationship between attitude of nurses with treatment of mild headinjury patients; (6) There is no relationship between the knowledge and attitudes of nursesand the handling of mild head injury patients treated Conclusion: There is significantrelationship between Knowledge with Treatment of mild head injury patients and there issignificant relationship between Attitude of Nurses with treatment of mild head injurypatients. The attitude and knowledge of a good nurse will increase the competence of nursesin handling head injury patients.